(untitled) (Revista científica Olimpia, 2018)
Frontotemporal dementia (DFT) and amyotrophic lateral sclerosis (ALS) have been classically considered neurodegenerative diseases that exclusively affect frontotemporal and motor areas, respectively. However, they have been shown to be multisystemic entities1 that overlap clinically and pathologically2 in 10 to 15% of cases3. This clinical continuum is reinforced at two levels: pathological, by the identification of the TDP43 protein (TAR DNA binding protein 43 kD) as the main component of ubiquitin-positive inclusions in ALS and in 50% of cases with FFT4,5; and at the genetic level by the identification of the expulsion of a repeated hexanucleotide in an intron of the gene C9ORF72 (chromosome 9p21) in 25% of the cases with familial ALS and 12% with familial DFT6,7. Patients with FTD who develop ALS have a more rapid evolution and worse prognosis, but there are no markers that allow the realization of an early diagnosis of DFT-ELA8. In this article we review the evidence of the overlap between DFT and ALS in terms of the clinical picture and its relationship with new genetic and pathological findings.